The effect of cuff width for determining limb occlusion pressure: A comparison of blood flow restriction devices - Weatherholt, A.; VanWye, W. R.; Lohmann, J.; Owens, J. (International Journal of Exercise Science, 2019)
136-143, 2019. The purpose of this study was to compare the standing lower extremity limb occlusion pressure (LOP) between two units. It was hypothesized that the Delfi unit, which utilizes a wider cuff (11.5 cm), would require significantly less LOP as compared to the KAASTU unit, which utilizes a narrow cuff (5 cm). Twenty-nine healthy participants (22 men, 7 women) mean age 24 years old (± 1.7 SD) volunteered. The procedure was identical for each cuff, completed with 5 minutes of rest in between. The cuff was placed on the proximal left thigh in the standing position. The initial pressure was set to 50 mmHg and then increased in 50 mmHg increments until complete arterial occlusion was achieved or the unit went to its maximum pressure. Arterial blood flow was determined by a mobile ultrasound measured at the left popliteal artery. Paired samples t-tests were used to determine differences in LOP (mmHg) between the Delfi and KAATSU unit cuffs. Significant differences were observed between the cuffs (wide: 239.4 mmHg vs. narrow: 500 mmHg; p < 0.001). We were able to achieve complete arterial occlusion with the wide cuff. The KAATSU unit reached maximum pressure with all participants, therefore we were unable to achieve complete arterial occlusion with the narrow cuff. Although achieving complete arterial occlusion is not indicated or safe for BFR training, relative pressures are used and determined as a percentage of LOP. Our study found that the relative pressure of the wide cuff is lower than the narrow cuff.